2007
DOI: 10.1093/toxsci/kfm227
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-Disrupting Activities In Vivo of the Fungicides Tebuconazole and Epoxiconazole

Abstract: The triazole fungicides tebuconazole and epoxiconazole were investigated for reproductive toxic effects after exposure during gestation and lactation. Rats were dosed with epoxiconazole (15 or 50 mg/kg bw/day) or tebuconazole (50 or 100 mg/kg bw/day) during pregnancy from gestational day (GD) 7 and continued during lactation until postnatal day (PND) 16. Some dams were randomly chosen for cesarean section at GD 21 to evaluate effects on sexual differentiation in the fetuses. Other dams delivered normally, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
128
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(145 citation statements)
references
References 27 publications
12
128
2
3
Order By: Relevance
“…There is insufficient evidence to assess the risk of tested pesticides to human health because of a lack of data. However, to our knowledge, all of the pesticides (with the possible exception of fenitrothion; Okahashi et al 2005;Turner et al 2002) identified as in vitro AR antagonists in our study have also been reported to have anti androgenic effects in vivo in animal models (Anway et al 2006;Gray et al 1999;Lambright et al 2000;McIntyre et al 2002;Ostby et al 1999;Sinha et al 2001;Taxvig et al 2007;Uzumcu et al 2004;Vinggaard et al 2005). We also identified 7 compounds that appeared to be androgenic because they stimulated activity in the absence of DHT.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…There is insufficient evidence to assess the risk of tested pesticides to human health because of a lack of data. However, to our knowledge, all of the pesticides (with the possible exception of fenitrothion; Okahashi et al 2005;Turner et al 2002) identified as in vitro AR antagonists in our study have also been reported to have anti androgenic effects in vivo in animal models (Anway et al 2006;Gray et al 1999;Lambright et al 2000;McIntyre et al 2002;Ostby et al 1999;Sinha et al 2001;Taxvig et al 2007;Uzumcu et al 2004;Vinggaard et al 2005). We also identified 7 compounds that appeared to be androgenic because they stimulated activity in the absence of DHT.…”
Section: Discussionmentioning
confidence: 53%
“…These compounds are newly formulated fungicides (dimethomorph, 2007; fludioxonil, 2008; fenhexamid, 2001), which are stable on food commodities (> 70% of the parent compound) and remain unchanged on the commodity when reaching the consumer (EFSA 2007(EFSA , 2010a(EFSA , 2010b. Dimethomorph and fenhexamid belong to the fungicide group of sterol bio synthesis inhibitors (Leroux 2004), as do the in vivo anti androgenic conazoles (e.g., Taxvig et al 2007) and imidazoles (Vinggaard et al 2005). A study of the sterol biosynthesis inhibitors imazalil, propi conazole, triadimefon, triadimenol, and prochloraz indicated that all inhibited aromatase in human placental microsomes (Vinggaard et al 2000), but to our knowledge, effects of dimethomorph and fenhexamid on steroido genesis in mammalian cells have not been assessed.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The developing foetal and infantile endocrine and reproductive systems are particularly 5 susceptible to endocrine disrupting substances [17,18,19]. Other conazoles which like miconazole, have been reported to inhibit CYP19 and testosterone synthesis in vitro, have been shown to disturb steroid synthesis in rat foetuses after prenatal exposure [20,21].…”
Section: Introductionmentioning
confidence: 99%